KETIMPANGAN GENDER DAN PERTUMBUHAN EKONOMI: STUDI KASUS PADA NEGARA-NEGARA ASIA TIMUR DAN PASIFIK - Napitupulu, Febiola; Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Scientific studies have not agreed about the effect of gender inequality on country’s economy. This quantitative research aims to identify the severity of gender inequality in East Asian and Pacific countries and to analyze the effect of gender inequality on the economic growth of those countries. A set of secondary panel data with the time span of fifteen years, i.e. from 2006 to 2020, from fifteen countries in the said region was acquired from World Economic Forum and World Bank and was analyzed using regression method. The results indicate that the inequality was very sever and that females are the less fortunate side. Furthermore, the gender inequality significantly influences the countries’ economic growth. Reduction of the inequality in economy, education, and politics enhances economic growth, while the reduction in health, in fact, decreases economic growth.